Political Financing and Political Corruption in Ghana’s Fourth Republic - Shiraz, S. (University of Ghana, 2023)
This thesis explores sculptures of Ewe spirituality and spirit-mediums generally referred to as Aklama. Based on ethnographic research, it examines local conceptualizations and narratives about Aklama across the Volta Region of Ghana. Cognisant of the fact that there are some commonality of traditions as well as significant variability in the indigenous religious practices among different Ewe-speaking groups, the research utilized a trifocal zoning of the region generally along the traditional dialects of the Ewedome, Tongu and Anlo. Adopting snowball sampling of informants within the designated zones, the study however prioritized personal experiences of individuals who engage in traditional religious rites as well as those who make or possessed Aklama figurines. Thus, the thesis analyses the figurations and engagements with Aklama in the contexts of the indigenous religion, and observances of customary rites. The study establishes that the phenomenon of Aklama is significantly undergirded by ascriptions to metaphysical origins of the human being as well as local beliefs about the essence of life and supernatural agency on kinship relations and social responsibilities. Worldviews among the Ewe thus conceptualized as a moral ecology, individuals owe to themselves the responsibility to optimally manifest their preordained destiny, uphold the common good of society and ultimately transition to the world of spirits as veritable ancestors. Doing due diligence to individuals’ spiritual agents and relations, Aklama enable the avenues for perceptibility and interactions with the otherwise unseen/non-sensible metaphysical agencies. Thus, considerations about Aklama are towards ensuring that individuals appropriately engage with requisite spirits or seek the assistance of the supernatural to successfully navigate this life. Particularly so in situations of misfortune, unaccounted illnesses and incessant experiences of blight, Aklama figurines serve as media through which humans negotiate with spirits for respite or alignment with benevolence. While similar worldviews and myths observed in the different zones about the universe as created by Mawu (the Supreme Being) serve to provide fairly common metaphysical foundation of Aklama, their figurations intersect with the peculiarities of individuals’ experiences and traditions of substantiating spiritual entities. In this vein, although there are significant similarities across the different zones about local conceptualizations of Aklama, there is far more variability both within and across the different zones resulting from experimenting and/or validating material forms in which spirits are manifested. Hence, prioritizing their attested functional efficiency over formal attributes, Aklama figurines are better evaluated within their contexts of engagements than any collectivised generalizations. That notwithstanding, the study provides important insights for provenance research on Ewe religious sculptures in general, and promises some prospects for better understating of Aklama figurines in museum collections.
PhD. Political Science
Keywords: Political Financing; Corruption; Ghana